Investigation of varietal resistance of some maize genotype against fall army (Spodoptera frugeperda) - Adewinle, A.A. (Lead City University, 2021)
The fall armyworm (FAW) has recently invaded and established itself as a major maize pest in Africa, causing yield losses of up to a third of annual maize production. The current study assessed several elements of resistance to FAW larvae feeding of 48 maize hybrids developed by IITA scientists in the laboratory, screen house, and field. The arrest and feeding of FAW neonate larvae in no-choice and choice trials, the growth of larvae-pupae in laboratory circumstances, and plant damage in a field experiment were all evaluated in this study. Although the tested maize hybrids did not show total resistance to FAW feeding, the study did identify differences in acceptability and preference when FAW larvae were offered a choice of cultivars. Furthermore, some of the hybrids' leaves had the least pupal weight and the lowest development index, implying that these maize hybrids many have antibiosis against FAW larvae. On the other hand, some of these hybrids had the highest growth index and had the largest pupal weight. In the field, neither natural nor artificial infestations resulted in statistically significant differences in plant damage scores between hybrids. Plant damage scores in some hybrids, on the other hand, tended to be lower in the last two samplings of the season compared to the first two rating under artificial and natural infestation. This study sheds light on FAW larval preferences and performance on several hybrid maize varieties, demonstrating that these characteristics differ between hybrids; nonetheless, high levels of resistance to larvae feeding were not discovered. FAW diets were statistically different from each in terms of pupal weight and larvae development but fecundity was not statistically different.